Marcel Duchamp, catalyseur de l’art contemporain - GAFSI, Habiba (Studia Universitatis Babeș-Bolyai Dramatica, 2016)
Marcel Duchamp: The Catalyst of Contemporary Art. Marcel Duchamp, qualified as the “anartist“, is considered as one of the important figures that influenced artists of the 20th century. Rejecting classical aesthetic references, his art is considered as choking as provocative. Many artists have adopted Duchamp’s move and denigrated all the anterior aesthetic criteria: Minimal art was oriented towards the Ready-made by using industrial objects that seem to have simple geometrical forms. The New Realism, also known as Neo-Dada, recollected what the dadaists have done in such a manner that the object generates its very space. Thus Duchamp paved the way to make any object be seen as a piece of art. Far away from the notion of the “Beautiful”, the work of art can be a simple manufactured or a pile of rubbish or reused objects. The importance is given not to the final work of art but to the system that has constituted it. Since then, the most recurrent question is no more “What’s art?” but “When there is art?” In other words, art is no more the resulting of an artistic creation, but it is a “fact” decided by the artist. In what way the Dadaist and Duchamp’s practices have influenced contemporary artistic practices? That’s the main question of the present paper.